"The Times They are A-Changin": Introducing the Section on Contemporary Child Psychoanalytic Education. Issue 1 (31st December 2022) - Sugarman, Alan
ABSTRACT: Bob Dylan's classic song, "The Times They are A-Changin, " is used to emphasize the importance for child analytic educators to address the urgency for the profession and those training future practitioners to accept the need for evolutionary change. Refusing to change our traditional ways of work and training will lead child analysis to go the way of the dinosaurs. There is already ample evidence that our field is dying as manifested in decreasing numbers of child analytic cases, child analytic candidates, and child analytic teachers and supervisors. This paper introduces a section devoted to various contemporary shifts and ideas that represent the sort of evolutionary changes required to ensure the survival and revival of child and adolescent psychoanalysis. These transformations involve expanding the role and presence of child analysis, integrating child and adult psychoanalytic curricula, redefining child analytic frequency, and incorporating parent work into child analytic theory of technique.